Дорадництво в умовах формування Agriculture (на прикладі ГО «Кіровоградська сільськогосподарська дорадча служба») - Анкудінов, Володимир Костянтинович; Ankudinov, Volodymyr (ЦНТУ, 2025)
У вступі обґрунтовано актуальність теми, визначено мету, об’єкт, і предмет дослідження. У першому розділі досліджено особливості еволюції концепцій сільського господарства, історичний аспект становлення та розвитку дорадництва, а також особливості дорадництва у контесті формування Agriculture 5.0 тощо. The introduction substantiates the relevance of the topic and defines the purpose, object, and subject of the study. The first chapter examines the peculiarities of the evolution of agricultural concepts, the historical aspect of the formation and development of advisory services, as well as the peculiarities of advisory services in the context of the formation of Agriculture 5.0 etc.
Consulting in the context of the formation of Agriculture (on the example of the NGO "Kirovohrad Agricultural Advisory Service")
Keywords: агробізнес; цифрова трансформація; ланцюги постачання агропродукції; цифровізація; оцифровка; інформаційне забезпечення; конкурентоспроможність; agribusiness; digital transformation; agricultural supply chains; digitalization; digitization; information support; competitiveness